Mastering Bitcoin : programming the Open Blockchain - Antonopoulos, Andreas M. (O'Reilly, 2017)
"Join the technological revolution that's taking the world of finance by storm. Mastering Bitcoin is your guide through the seemingly complex world of bitcoin, providing the knowledge you need to participate in the internet of money. Whether you're building the next killer app, investing in a startup, or simply curious about the technology, this revised and expanded second edition provides essential detail to get you started. Bitcoin, the first successful decentralized digital currency, is still in its early stages and yet it's already spawned a multi-billion dollar global economy. This economy is open to anyone with the knowledge and passion to participate. Mastering Bitcoin provides the knowledge. You simply supply the passion."- Resumé vydavatel